'Madat makan orang'; opium eats people: Opium addiction as a public health issue in late colonial Java, 1900–1940. (June 2020) - Wahid, Abdul
Abstract : By the 1890s the Dutch had noticed the escalation of opium addiction in colonial Indonesia. They believed that opium consumption had brought about health problems and other negative socioeconomic effects. Yet, the profitability of opium took precedence over its negative social effects in the Dutch East Indies government's policy, which until the end of the 1920s made almost no substantial efforts to address addiction. It was nongovernmental organisations which took the initiative to install medical facilities for addicts and launch diverse anti-opium campaigns. These organisations marked the rise of modern philanthropic activism in the field of public health as part of the flourishing sociopolitical movements of that time. They also represent the nascent civil society in late colonial Indonesia.